Power plant entrainment : a biological assessment - Schubel, J. R.; Marcy, Barton C. (Academic Press, 1978)
A summary of the workshop held by the Ad Hoc Committee on Entraipment on January 17-21 and March 20-22, 1977 at the Marine Sciences Research Centre, State University of New York at Stony Brook.